MAJOR AMERICAN ENGLISH DIALECTS - Toguspay, A.M. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
This article is dedicated to the study of Major American English Dialects. The historical background, lexical, phonological, and grammatical differences of American Dialects are briefly given.
Keywords: dialect; American dialects; history; lexis; phonetics; grammar